Sustainable Development and Agro-Industrial Farming of Oil Palm in Norte de Santander, Colombia - Manzano López, Dennys Jazmín; Botello Sanchez, Eder Alexander; Zambrano Miranda, Mario de Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The agro-industrial farming of oil palm has been considered in various parts of the world and by several national and regional governments of Colombia, as a productive commitment to development and competitiveness. However, its promotion, results and effects must be compared in light of the 2030 Agenda for Sustainable Development Goals (SDG), and thereby direct its main benefits in terms of sustainable development. Based on the above, this research aims to estimate the level of sustainable development of the agro-industrial cultivation  of oil palm in Norte de Santander. For this, first of all, from the four dimensions of sustainable development, the Agricultural Production Units (UPA, by its acronym in Spanish) of palm growers of the state are characterized; and secondly, the level of sustainable development of each UPA is estimated by the Multidimensional Index of Sustainable Development (MISD). The results suggest that the activity does not seem to offer conditions that promote development with prosperous economic growth, which could be socially inclusive and environmentally sustainable within the framework of good governance; in other words, the activity does not fully promote sustainable development for the palm growers of Norte de Santander.